Detection of triploidy at 11–14 weeks' gestation: a cohort study of 198 000 pregnant women. (9th October 2013) - Engelbrechtsen, L.; Brøndum‐Nielsen, K.; Ekelund, C.; Tabor, A.; Skibsted, L.; ,
ABSTRACT: Objectives: To assess the detection rate of triploidy at first‐trimester screening for trisomy 21 and evaluate outcome in triploid pregnancies . Methods: From 2008 to 2011, 198 427 women with singleton pregnancies underwent first‐trimester screening between 11 + 2 and 14 + 0 weeks' gestation. Screening parameters included nuchal translucency, maternal serum free β‐human chorionic gonadotropin (β‐hCG) and pregnancy‐associated plasma protein‐A (PAPP‐A). In all triploid fetuses, these parameters were re‐evaluated. Karyotypes were established by invasive testing (chorionic villus sampling or amniocentesis) or postabortem and obtained from the Danish Cytogenetic Central Register and the Danish Fetal Medicine Database . Results: A total of 30 triploid fetuses underwent first‐trimester screening. Twenty‐five were diagnosed as a result of abnormal first‐trimester scan findings, a detection rate of 83.3%. Twenty‐three fetuses were identified due to a high risk for trisomy 13, 18 or 21 and two fetuses due to structural abnormalities. The incidence of triploidy at first‐trimester screening was 1:6614. A smaller crown–rump length than that estimated by date of last menstrual period was found in 95% of the fetuses with data available for evaluation. Eight fetuses had a larger biparietal diameter than expected for gestational age. Fetuses with a 69, XXX karyotype had significantly lower multiples of the median values for β‐hCG and PAPP‐A than did 69, XXY fetuses ( P  = 0.045 and P  = 0.02 forβ‐hCG and PAPP‐A, respectively). No infants with triploidy were born in the study period. Among the triploid gestations detected on first‐trimester screening, 20 (80.0%) women chose termination of pregnancy, four (16.0%) had spontaneous miscarriage and one (4.0%) was stillborn . Conclusion: First‐trimester screening for trisomy 21 also provides a high detection rate for triploidy. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .